Reading engagement, achievement and learning experiences through kahoot - Rachman, Dzul; Soviyah, Soviyah; Fajaruddin, Syarief; Pratama, Rio Arif (LingTera, 2020)
Side-synchronizing between English reading teaching and learning and latest technology is highly encouraged to happen nowadays in order to get better learning achievement. The main purpose of this study was to find out the effect of Kahoot! on reading comprehension. This study involved 244 students of one of the established private universities in East Kalimantan. Data analysis was conducted using descriptive statistics in the form of frequency, mean, standard deviation and t – test. The results showed that the students' reading comprehension taught using Kahoot! was higher than that of those without Kahoot!. Furthermore, their cognitive, psychomotor and affective learning attitudes showed positive and significant effects as well. Based on the findings, it implies that online media like Kahoot! is strongly recommended to be used in reading teaching and learning process. It is expected that the finding would enrich and enlighten the relevant literature of the area.